2001
DOI: 10.1097/00004770-200107000-00006
|View full text |Cite
|
Sign up to set email alerts
|

p53 Protein Expression in Odontogenic Cysts

Abstract: p53 protein seems to be related to the suppression of cell proliferation. p53-positive tissues seem to have a higher proliferative activity than p53-negative ones. Odontogenic keratocyst (OKC) has a different behavior from other types of cysts because it is more aggressive, with a tendency to recurrence. Twenty-two dentigerous cysts, 24 radicular cysts, and 20 OKCs were used in the present study. Two dentigerous cysts (9.1%), 2 radicular cysts (8.3%), and 9 OKCs (45%) expressed the p53 protein. The differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
0
4

Year Published

2005
2005
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 25 publications
9
42
0
4
Order By: Relevance
“…In this study, p53 immunoexpression was positive in 50% of OKCs, 40% of dentigerous cysts and radicular cysts, and 30% of ameloblastomas, but without statistically significant differences among them. Conversely, Piatelli et al (19), also found a higher p53 expression in odontogenic keratocysts than in dentigerous and radicular cysts, and differences between the three groups were stastistically significant. Ogden et al (17) using CM-1 antibody reported that 5 of 12 odontogenic keratocysts expressed P53, while Lombardi et al (20) with the same clone CM-1 found p-53 in 50% of their OKCs, including non-recurrent, recurrent and associated with the basalcell nevus syndrome.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this study, p53 immunoexpression was positive in 50% of OKCs, 40% of dentigerous cysts and radicular cysts, and 30% of ameloblastomas, but without statistically significant differences among them. Conversely, Piatelli et al (19), also found a higher p53 expression in odontogenic keratocysts than in dentigerous and radicular cysts, and differences between the three groups were stastistically significant. Ogden et al (17) using CM-1 antibody reported that 5 of 12 odontogenic keratocysts expressed P53, while Lombardi et al (20) with the same clone CM-1 found p-53 in 50% of their OKCs, including non-recurrent, recurrent and associated with the basalcell nevus syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…Ogden et al (17) using CM-1 antibody reported that 5 of 12 odontogenic keratocysts expressed P53, while Lombardi et al (20) with the same clone CM-1 found p-53 in 50% of their OKCs, including non-recurrent, recurrent and associated with the basalcell nevus syndrome. Piatelli et al (19), employing the clone DO7 found p-53 expression in 45% of 20 odontogenic keratocysts. We have found the same percentage of positively stainded cells in OKCs as these authors on the contrary we have found higher positivity rates in dentigerous cysts and radicular cysts.…”
Section: Discussionmentioning
confidence: 99%
“…En conséquence, certains auteurs se sont orientés vers l'étude de l'expression de la P53 en cherchant à établir l'existence d'une corrélation entre l'expression de cette protéine et la survenue récidive des KKO [4][5][6]. Dans cette étude, 10 cas étaient positifs pour la P53 ; comme cela a déjà été précisé [4,[6][7][8][9][10][11], cette positivité a été observée dans les couches suprabasales de l'épithélium.…”
Section: Discussionunclassified
“…La comparaison de l'expression de la P53 dans les diffé-rentes formes cliniques n'a pas montré de différence statistiquement significative (chi-2 = 0.191). Nos résultats concordent avec ce qui a déjà été publié [3,8,9,11]. Dans les KKO, il existe une l'hyperexpression de la P53 par rapport aux autres kystes odontogénes.…”
Section: Discussionunclassified
“…Relatively frequent was focus on the significance of suppressor gene p53 expression 6 . The results showed that immunohistochemically detected overexpression of p53 was caused more by overproduction or increased stabilization of the protein than gene amplification.…”
Section: Histopathologymentioning
confidence: 99%